Effectiveness of Trastuzumab in First-Line HER2+ Metastatic Breast Cancer After Failure in Adjuvant Setting: A Controlled Cohort Study. (29th October 2014) - Negri, Eva; Zambelli, Alberto; Franchi, Matteo; Rossi, Marta; Bonifazi, Martina; Corrao, Giovanni; Moja, Lorenzo; Zocchetti, Carlo; La Vecchia, Carlo
Abstract: Background: The evidence supporting the use of trastuzumab (T) in a metastatic setting comes from studies that included (almost) only patients who never received prior T. We investigated the effectiveness of T as first-line therapy for metastatic breast cancer (mBC) in women previously treated with T in the adjuvant setting. Materials and Methods: By using record linkage of five administrative health care databases of Lombardy, Italy, we identified 2, 046 women treated with T for early breast cancer (eBC) in 2006–2009, 96 of whom developed a metastasis and were retreated with T in first-line treatment for mBC (treatment group). We compared the overall survival (OS) of these women with that of 197 women treated with T in first-line treatment for mBC, who were treated with therapies other than T for early disease (control group). We computed Kaplan-Meier 2-year OS and used a proportional hazard model to estimate the multivariate hazard ratio (HR) of death in the intervention group compared with the control group, adjusted by age, use of endocrine therapy, and site of metastasis. Results: Two-year OS was 60.0% in the treatment group and 59.5% in the control group. The adjusted HR of death in the treatment group compared with the control group was 0.79 (95% confidence interval, 0.50–1.26). Conclusion: Our data provide convincing evidence that the outcome of women receiving first-line T treatment for mBC after T failure in the adjuvant setting is comparable to that of women not receiving T for eBC. These data are of specific interest, given the unavailability of data from randomized clinical trials. Abstract : The effectiveness of trastuzumab (T) as first-line therapy for metastatic breast cancer (mBC) in women previously treated with T in the adjuvant setting was investigated. The outcome of women receiving first-line T treatment for mBC after T failure in the adjuvant setting is comparable to that of women not receiving T for early breast cancer.